Multidimensional engagement and store performance: The perspective of frontline retail employees. Issue 5 (11th June 2018) - Suhartanto, Dwi; Brien, Anthony
Abstract : Purpose: The purpose of this paper is to examine the effect of multidimensional engagement (job engagement and organization engagement) on retail stores' performance directly and indirectly through job performance and job satisfaction. Design/methodology/approach: Data were collected from frontline retail store employees. A variance-based structural equation modeling (PLS) is used to examine the relationships between multidimensional engagement, job performance, job satisfaction, and store performance. The bootstrap method was applied to examine the mediation role of job performance and job satisfaction. Findings: This study supports the existence of a multi-dimension engagement consisting of job engagement and organization engagement and the relationship between these engagements. Further, this study reveals that job engagement and organization engagement are important determinants of store performance. Practical implications: This study provides an avenue for retail store managers to increase their store performance through the development of employee engagement. To improve the store performance, this study suggests that store managers provide a challenging job and encourage employees to use their creativity in serving customers. It is also important to store managers to support employees in performing their jobs, including procedural fairness in stores. Originality/value: This study is one of the first attempts to examine the effect of multidimensional engagement on organization performance at a business unit level (retail store).